2015
DOI: 10.1016/j.jand.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Monitor Food and Nutrition from “Factory to Fork”

Abstract: Background Accurate, adequate, and timely food and nutrition information is necessary in order to monitor changes in the US food supply and assess their impact on individual dietary intake. Objective Develop an approach that links time-specific purchase and consumption data to provide updated, market representative nutrient information. Data and Methods We utilized household purchase data (Nielsen Homescan, 2007–2008), self-reported dietary intake data [What We Eat in America (WWEIA), 2007–2008], and two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Because NHANES does not consistently collect detailed information about brands of products consumed by respondents, it is not possible to determine how changes in purchases for different brand categories across various subpopulations relate to diet and health outcomes. NHANES also does not capture many of the product reformulations ongoing in the CPG sector (48). However, this article shows that storebought foods and beverages are large contributors of calories consumed.…”
Section: Discussionmentioning
confidence: 81%
“…Because NHANES does not consistently collect detailed information about brands of products consumed by respondents, it is not possible to determine how changes in purchases for different brand categories across various subpopulations relate to diet and health outcomes. NHANES also does not capture many of the product reformulations ongoing in the CPG sector (48). However, this article shows that storebought foods and beverages are large contributors of calories consumed.…”
Section: Discussionmentioning
confidence: 81%
“…39 Although this study uses the most recently released USDA equivalents database to estimate added sugars, the USDA food composition tables are not updated as quickly as new products or product reformulations emerge. 33, 40, 41 Further, this analysis does not have the ability to determine whether some of the decline in added sugars may come from a switch to sweeteners not currently counted as added sugars by the USDA databases, such as fruit juice concentrates. One recent study found that in 2004–2009 over 11% of the foods and beverages in the US packaged food supply contained fruit juice concentrates.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no other existing US database has integrated comprehensive sales-weighted barcode-specific nutrition information into a time-specific food composition table for use with dietary intake data (Ng and Dunford, 2013; The Food Monitoring Group, 2013; Slining et al, 2015). By identifying differences in nutrient content estimated using the Crosswalk-enhanced vs standard FNDDS, our database can help identify food groups to target for updating in FNDDS; examples identified in our study include yogurt and fried potatoes.…”
Section: Discussionmentioning
confidence: 99%
“…RDs made all linkages manually after reviewing the UPC’s item description, brand name, attributes, ingredients, and marketing, as described previously (Slining et al, 2015). To standardize the linkages, the research team jointly determined the decision rules to apply when matching UPCs to each FNDDS foodcode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation